Dietary influence on adiponectin in patients with type 2 diabetes. (2nd April 2021) - Bozzetto, Lutgarda; Polito, Rita; Nigro, Ersilia; Prinster, Anna; Della Pepa, Giuseppe; Costabile, Giuseppina; Vetrani, Claudia; Vitale, Marilena; Daniele, Aurora; Rivellese, Angela Albarosa; Annuzzi, Giovanni
Abstract: Background: Here, we evaluate the effects of a diet rich in low‐glycaemic index carbohydrates and fibre (CHO/Fibre diet) or monounsaturated fatty acids (MUFA diet), on fasting and postprandial adiponectin concentrations and their relationship with the beneficial effects of the experimental diets on postprandial glucose metabolism and liver fat in type 2 diabetes (T2D). Methods: Fasting and postprandial adiponectin plasma concentrations were measured before and after dietary interventions in the participants to a randomized controlled trial (NCT01025856), wherein 37 men and 8 women with T2D, aged 35‐70 years, followed a CHO/Fibre diet or a MUFA diet for an 8‐week period. Hepatic fat content by 1 H NMR and fasting and postprandial plasma glucose and insulin measurements were also available. Results: Fasting adiponectin plasma levels did not change after both diets. Postprandial adiponectin significantly increased after the CHO/fibre diet (9.9 ± 1.6 μg/mL vs. 10.8 ± 2.3 μg/mL; P  = .033) but not after the MUFA diet (10.6 ± 1.8 μg/mL vs. 10.6 ± 1.6 μg/mL; P  = .935) with a significant difference between changes ( P  = .035). In the combined CHO/Fibre and MUFA groups, fasting and postprandial adiponectin significantly and inversely correlated with postprandial insulin iAUC at baseline and after intervention, and with liver fat content after intervention. Conclusions: A diet rich in CHO/Fibre increased postprandial plasma adiponectin significantly more than a MUFA diet in patients with T2D. Independently of diet, adiponectin levels associated with postprandial insulin concentrations. The dietary interventions modulated the relationship between adiponectin and liver fat.